Movement of Overlying Strata and Mechanical Responses of Shallow Buried Gas Pipelines in Coal Mining Areas - Jiashu Han; Zhanguo Ma; Junyu Sun; Peng Gong; Pengfei Yan; Chuanchuan Cai; Mingshuo Xu; Tianqi She (Applied Sciences)
Damage to buried gas pipelines caused by mining activities has been frequently reported. Based on a case study from the Central China coal mining area, this research employs a scaled model experiment to investigate the movement of overlying strata in a room-and-pillar mining goaf. Distributed optical fiber strain sensors and thin-film pressure sensors were used to simultaneously measure the stress variations in the pipeline and changes in the soil pressure surrounding it. As the mining recovery rate increased from 50% to 86%, the maximum displacement of the overburden sharply escalated from 33.55 mm to 79.19 mm. During surface subsidence, separation between the pipeline and surrounding soil was observed, leading to the formation of a soil-arching effect. The development of the soil-arching effect increased soil pressure on the top of the pipeline, while soil pressure at the bottom of the pipeline increased on the outer side of the subsidence area and decreased on the inner side. Three critical sections of the pipeline were identified, with the maximum stress reaching 1908.41 kPa. After the completion of mining activities, pipeline collapse occurred, leading to a weakening of the soil-arching effect. Consequently, both stress concentration in the pipeline and soil pressure decreased. The probability integral method was corrected by incorporating the fracture angle, which enabled the determination of the location of maximum surface subsidence curvature, found to be close to the three failure sections of the pipeline.